Investigation of the accuracy of deep inspiration breath hold left-sided breast cancer radiotherapy using a surface guiding system - S. Nankali; A. Zirak; A. Movafeghi; P.R. Poulsen (مجله علوم و فنون هسته‌ای, 2020)
Vision-RT system is one of the most effective methods for real-time estimation of target location in external beam radiotherapy. Vision-RT tracks the patient’s surface before and during radiation therapy to improve treatment accuracy. Using proprietary 3D stereo camera units, Vision-RT system tracks the skin surface, compares it to the ideal position, and can automatically signal to the treatment delivery system. The purpose of this study is to investigate the accuracy of Vision RT guided deep inspiration breath-hold left-sided breast cancer radiotherapy. Five patients with left-sided breast cancer were treated by Vision RT guided deep inspiration breath-hold at Aarhus university hospital. Based on the results, in one out of five patients, the undesired heart extended to 0.6-0.9 cm into the treatment fields in 5 out of 15 treatment fractions. Moreover, the required PTV margin to account for patient setup error and intra-fractional error of the first and second treatment field was 2.38 mm, 3 mm and 4.12 mm, respectively.